BS EN ISO 4628-5. Paints and varnishes. Evaluation of degradation of coatings. Designation of quantity and size of defects, and of intensity of uniform changes in appearance. Part 5. Assessment of degree of flaking (23rd December 2021) - British Standards Institution,
No abstract available